2011
DOI: 10.1002/cjoc.201100045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐tumor Evaluation of B‐ring Modified Caged Xanthone Analogues of Gambogic Acid

Abstract: Gambogic acid (GA, 1), the most prominent member of Garcinia natural products, has been reported to be a promising anti-tumor agent. Previous studies have suggested that the planar B ring and the unique 4-oxa-tricyclo-[4.3.1.0 3,7 ]dec-2-one caged motif were essential for anti-tumor activity. To further explore the structure-activity relationship (SAR) of caged Garcinia xanthones, two new series of B-ring modified caged GA analogues 13a-13e and 15a-15e were synthesized utilizing a Claisen/Diel-Alder cascade re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The unsaturated double bond at C-8/8a appears to significantly contribute to apoptosis induction and antitumor activity [99,109,159,160]. Additionally, the Theodorakis and You research groups have independently reported that the gem-dimethyl groups at C-28 and C-33 are crucial for these compounds' cytotoxicity [97,161]. However, the presence of a C-33 gem-dimethyl has been found to be inessential for cytotoxicity against HepG2 cells; substitution of this moiety by hydrogen atoms is tolerated but oxidation of C-33 to carbonyl have been found to decrease the activity [104].…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…The unsaturated double bond at C-8/8a appears to significantly contribute to apoptosis induction and antitumor activity [99,109,159,160]. Additionally, the Theodorakis and You research groups have independently reported that the gem-dimethyl groups at C-28 and C-33 are crucial for these compounds' cytotoxicity [97,161]. However, the presence of a C-33 gem-dimethyl has been found to be inessential for cytotoxicity against HepG2 cells; substitution of this moiety by hydrogen atoms is tolerated but oxidation of C-33 to carbonyl have been found to decrease the activity [104].…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…In contrast, the aromaticity of the A ring must be maintained, because oxidation of the A ring to quinone leads to a complete loss of activity [163]. The presence of a hydroxyl group at the C-1 position is an important structural feature for antitumor activity [102,161,163] and has been found to enhance IKKβ inhibitory activity [158]. Activity is preserved when the hydroxyl group is methylated or acylated [159], but replacing the hydroxyl group with a prenyl group is unfavorable [161].…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [ 113 , 114 , 115 , 116 ] synthesized a series of caged xanthone derivatives to improve the physicochemical properties and in vivo cytotoxic potency. For that, they relied on MAD28 synthesis and characterization of the derivatives.…”
Section: Synthetic Chiral Derivatives Of Xanthonesmentioning
confidence: 99%
“…Some interesting SAR considerations have been highlighted, such as the importance of the periphery gem-dimethyl groups in maintaining the anti-tumor activity, the effect of the substituent at C-1 position of B-ring on activity, since hydroxyl group at C-1 position enhanced the potency while prenyl group reduces it, and, that the change of hydroxyl or prenyl groups in carbons C-2, C-3 and C-4 had no significant effect on the anti-tumor activity. These events indicated that referred sites can be used to improve drug-like properties [ 114 ].…”
Section: Synthetic Chiral Derivatives Of Xanthonesmentioning
confidence: 99%